Characteristics of bilateral versus unilateral temporal encephalocele-associated epilepsy. (October 2019) - Paule, Esther; Freiman, Thomas M.; Strzelczyk, Adam; Reif, Philipp S.; Willems, Laurent M.; Wagner, Marlies; Zöllner, Johann Philipp; Rosenow, Felix
Highlights: Bilateral temporal encephaloceles represent a potentially curable cause of epilepsy. Typical for BTE-associated epilepsy are a higher age at onset and drug-resistance. Standardized diagnostic workup for TLE patients with unknown etiology is advisable. Abstract: Purpose: To characterise bilateral temporal encephalocele (BTE)-associated epilepsy relative to unilateral temporal encephalocele (UTE)-associated epilepsy as a rare but curable cause of structural epilepsy using demographics, epilepsy status and imaging findings. Method: In this single-centre retrospective study we included all patients from June 2015 to August 2018, who suffered from epilepsy and were diagnosed with a temporal encephalocele. Data were systematically collected and analysed for differences between BTE and UTE. Results: Seventeen epilepsy patients diagnosed with temporal encephaloceles (TE) were identified. One-third exhibited BTE. The age of epilepsy onset was higher in patients with BTE compared to UTE (median 51 vs. 37 years, p = 0.074). Latency between epilepsy diagnosis and definitive TE diagnosis differed considerably with a median five-fold shorter duration for the BTE-group when compared to the UTE-group (2–10 years, p = 0.02). Five of seven (81%) patients with BTE were pharmacoresistant, while this applied to only five out of ten (50%) patients with a UTE. Conclusion: When compared to UTE-associated epilepsy, BTE-associated epilepsy is characterised by a later age at onset, shorter delay in TE diagnosis and more frequent drug-resistance. As epilepsy surgery is a valid treatment option for both syndromes, a standardised diagnostic workup should be implemented for temporal lobe epilepsy (TLE) patients with unknown aetiology to facilitate early detection of UTE and BTE.